Arts-Based Research: A Critique and a Proposal - Jagodzinski, Jan; Wallin, Jason (Rotterdam Sense, 2013)
A provocative book, an important book! jagodzinski | Wallin's 'betrayal' is in fact a wake-up call for art-based research, a loving critique of its directions. jagodzinski Wallin's reference is the question 'what art can do' - not what it means. Theirs is an ultimate affi rmation that uncovers the singularities that compose and give consistency to art not as an object, but as an event. Their betrayal consists in an affirmation of life and becoming, positing a performative 'machinics of the arts' which is in absolute contraposition with the hegemonic discourse of art and|as an object of knowledge and representation. This does not only concern academia, but also politics and ethics - an untimely book that comes just at the right time! Bernd Herzogenrath, Goethe Universität Frankfurt am Main (Germany), author of An American Body|Politic. A Deleuzian Approach, and editor of Deleuze & Ecology and Travels in Intermedia[lity]: ReBlurring the Boundaries. jagodzinski | Wallin have written a challenging book on the theme of betrayal which aims to question the metaphysical ground of the practice of many arts educators and researchers. Dismantling the notion of praxis which assumes a prior will as well as the pervasive notion of the creative and refl exive individual, they revisit the notion of poiesis and the truth of appearing in order to advocate the centrality of becoming in pedagogical relations. Is it possible to develop pedagogies beyond those images of thought that attenuate learners, teachers and researchers? We need a new image of thought, or better, a thought without image, and this book asks us to take up the challenge. Dennis Atkinson, Director of the Centre for the Arts and Learning, Department of Educational Studies, Goldsmiths University of London, author of Art Equality and Learning; Pedagogies Against the State.
Keywords: Artistic research